Effects of Selective Withdrawal on Hydrodynamics of a Stratified Reservoir - Çalışkan, Anıl; Elçi, Şebnem; Elçi, Şebnem (Springer Verlag, 2009)
In water supply reservoirs, selective withdrawal is commonly implemented to control released water temperature for quality purposes. This study investigated the effects of selective withdrawal on hydrodynamics of a stratified reservoir through numerical modeling and analytical analysis. A 3-D hydrodynamic model was applied where observations of water temperature time series recorded every 30 min at the thermocline and measured temperature profiles along the water column were used to validate the numerical model. The effect of selective withdrawal from four outlets located along the water intake structure of Tahtali Reservoir in Turkey on water temperatures was investigated and the effects on thermal stratification structure were discussed. Withdrawal of the water at the bottom outlet was found to be the most effective choice encouraging the mixing of the water column and thus reducing anoxia. The results of this study can be used to guide the further investigations in stratified lakes for better management practices.
Keywords: EFDC; Hydrodynamics; Outflow dynamics; Stratification; Tahtali Reservoir; Withdrawal effects